دور التجديد الاستراتيجي في تحسين جودة الحياة الوظيفية بمستشفى جامعة العلوم والتكنولوجيا-أمانة العاصمة – صنعاء - القرص عبد الفتاح علي (Journal of Amran University, 2023)
This research aimed to examine the role of the strategic renewal in its dimensions (exploration, opportunity exploitation, entrepreneurship, participatory leadership) in improving the occupational life quality in its dimensions (participation in decision-making, job safety and stability, balance between personal and occupational life, material work conditions) at the University of Science and Technology Hospital - Sana'a. The analytic descriptive research was used. A questionnaire was used to collect data from the research sample with a number of (98) who held leadership positions, represented by (general/deputy manager, directors of administration offices, department heads, unit officers, consultant doctors). The results showed that there is a statistically significant role for strategic renewal in achieving the occupational life quality at the University of Science and Technology Hospital. The research recommended to enhance the occupational life quality level in all dimensions by studying and analyzing factors affecting the occupational life quality of the hospital staff and the personal and occupational variables affecting them because of their impact on the staff performance. The hospital under study should pay more attention to the practices, behaviors and characteristics of the strategic renewal because of their role in achieving superiority over other competitors.